Keanekaragaman Vegetasi Tanaman Obat di Hutan Pendidikan Universitas Sumatera Utara Kawasan Taman Hutan Raya Tongkoh Kabupaten Karo Sumatera Utara - Riwanda Sembiring; Budi Utomo; Ridwanti Batubara (Program studi Kehutanan USU, 2013)
This study aims to determine the function and the diversities of medicinal plant that contained at the educational Forest of North Sumatra University, Bukit Barisan Forest Park, Tongkoh village, District of Karo, North Sumatera. This study was held in May to August 2012. The study was conducted at such altitude categories: <1000 masl; 1000 - 1500 masl, and ≥ 1500 masl. Observations were made on five different lines in each height category. Observation path length is 100 m. Determination of the first line is done by purposive sampling method, the path is determined by systematic sampling plots spaced 200 m. Observation and collection of medicinal plants using sampling methods plot measuring 20 m x 20 m. Observations conducted exploratory medicinal plants. The number of medicinal plant species found in each height category successive 34 species, 30 species, and 28 species. Total all kinds of medicinal plants found are 38 species. Keywords: Diversity of Medicinal Plants, Medicinal Plants, Educational Forest of North Sumatera University, TAHURA Bukit Barisan.